Análise sobre a morosidade do poder Judiciário brasileiro e propostas de intervenção - Costa, Anderson Yagi (2018)
Morosity is the main problem of the Brazilian Judiciary and has affected it for more than a century. In spite of the importance of this problem, there is a scarcity of studies in the literature that analyze, in a scientific way and with methodology, the possible causes of the slowness and that propose viable and manageable solutions. This study aims to verify if certain reported causes actually contribute to the slowness and, thus, to propose a viable solution. The survey of the possible causes was carried out through a review of the literature and the analysis of satisfaction surveys conducted at the Goiás State Court of Justice (TJGO). After identifying 43 (fortythree) possible causes, the increase in demand and the lack of magistrates / servers were selected for an analysis. After the analysis, using a methodology imposed by the National Justice Council - CNJ, it was found that the current number of magistrates and servants of the TJGO is enough to give flow to the demand. Thus, the redistribution of the labor force was proposed as a way to better serve the lossmaking judicial units.